A Low-Cost Instrument to Monitor Sulphur Dioxide Emissions Based on The DOAS Method - Zen, Nur; Huboyo, Haryono Setiyo; Romadhon, Moch. Syarif; Fatkhurrahman, Januar Arif; Amrulah, Sidna Kosim (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
Various techniques to measure SO2 concentration based on Differential Optical Absorption Spectroscopy (DOAS) have been widely developed and applied for various measurements. However, most of the applications are still relatively expensive. Some efforts have been made to reduce the cost by using Ultraviolet Light Emitting Diodes (LEDs) as light sources, showing promising results. Further reductions can be possibly made by providing an alternative to replace high spectral resolution spectrometers widely used in DOAS applications since those spectrometers are commercially expensive. This paper studies the feasibility of a DOAS instrument using a low-cost spectrometer and UV-LEDs as light sources. The resolution of the spectrometer is 0.7 nm. With this resolution, it is expected that the instrument hardly captures narrow band structures of SO2 optical absorption in the spectral range between 280 nm and 320 nm when measuring SO2 gas concentration lower than the limits of SO2 emissions regulated by the Indonesian government. To compensate for this drawback, narrow and broad bands of optical absorption structures are considered in the data analysis to achieve a detection limit far below the regulated limits. To capture the broadband structures, four UV-LEDs are used to cover spectral absorption from 250 nm to 320 nm. The instrument was calibrated using eight different standard concentrations of SO2. The correlation between the readings and the standard concentrations is high, indicated by the Pearson correlation coefficient of 0.9999. It was also found that the lowest concentration the instrument can distinguish from blank samples or the Limit of Detection is 16 ppm. However, the instrument can precisely measure concentrations higher than or equal to 25 ppm with a standard deviation of less than 10% of the mean concentration measured from five measurements. This is far below the required legal limits, below 229 ppm. After the calibration, the DOAS instrument was used to measure SO2 sampled from the emission of burning coals. To compare, a commercial SO2 sensor was used to measure the same gas. The results indicate that the difference in the readings between the two instruments is around 6% of the concentration.